2001
DOI: 10.1128/jcm.39.9.3122-3128.2001
|View full text |Cite
|
Sign up to set email alerts
|

Seven Human Immunodeficiency Virus (HIV) Antigen-Antibody Combination Assays: Evaluation of HIV Seroconversion Sensitivity and Subtype Detection

Abstract: In this study, we evaluated the performance of two prototype human immunodeficiency virus (HIV) antigen-antibody (Ag-Ab) combination assays, one from Abbott Laboratories (AxSYM HIV Ag-Ab) and the other from bioMerieux (VIDAS HIV Duo Ultra), versus five combination assays commercially available in Europe. The assays were Enzygnost HIV Integral, Genscreen Plus HIV Ag-Ab, Murex HIV Ag-Ab Combination, VIDAS HIV Duo, and Vironostika HIV Uniform II Ag-Ab. All assays were evaluated for the ability to detect p24 antig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
69
2
2

Year Published

2006
2006
2015
2015

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 78 publications
(78 citation statements)
references
References 26 publications
3
69
2
2
Order By: Relevance
“…In other studies, no evidence was found for a second diagnostic window due to the impaired sensitivity of the antibody detection module of different 4th generation HIV assays [13,17]. These studies did not observe a significant drop in the measured index values or negative results in the transient period between the decline of antigenemia and the beginning of the seroconversion.…”
mentioning
confidence: 63%
See 2 more Smart Citations
“…In other studies, no evidence was found for a second diagnostic window due to the impaired sensitivity of the antibody detection module of different 4th generation HIV assays [13,17]. These studies did not observe a significant drop in the measured index values or negative results in the transient period between the decline of antigenemia and the beginning of the seroconversion.…”
mentioning
confidence: 63%
“…No seronegativity for different samples was observed, but the index values dropped near the cut off [13]. This was not observed for this case, instead, the levels of p24 antigen did not dropped in two days, but increased and then the antibodies appeared.…”
mentioning
confidence: 78%
See 1 more Smart Citation
“…These assays provide an advantage for detection of infection during the window period prior to seroconversion since the diagnostic window may be reduced by an average of 5 days relative to an IgM-sensitive EIA (Fiebig et al, 2003;Weber et al, 1998). However, some fourth-generation assays showed low sensitivity in the detection of p24 antigen from some non-subtype B HIV-1 strains (A, C, F, H, CRF01_AE, O) (Kwon et al, 2006;Ly et al, 2007;Ly et al, 2004;Ly et al, 2001;Weber, 2002). This low sensitivity in antigen detection may be attributed to differences in viral epitopes of the different HIV genetic forms which may not be recognized by the monoclonal antibody used in the assay (Plantier et al, 2009a).…”
Section: Immunoassaysmentioning
confidence: 86%
“…Key epitope(s) targeted by these assays might be modified or eliminated by the occurrence of natural polymorphisms within the IDR region associated with the genetic variation of HIV-1, ultimately leading to reduced sensitivity or lack of antibody detection (Brennan et al, 2006;Gaudy et al, 2004). A few cases of false-negative results involving, for example, subtypes B, C, and F, and resulting from major mutations of the IDR epitope have been described (Aghokeng et al, 2009;Gaudy et al, 2004;Ly et al, 2007;Ly et al, 2004;Ly et al, 2001;Zouhair et al, 2006). Earlier analysis of specimens from patients infected with group O viruses revealed that some commercial immunoassays failed to detect group O infections (Eberle et al, 1997;Loussert-Ajaka et al, 1994;Schable et al, 1994;Simon et al, 1994).…”
Section: Immunoassaysmentioning
confidence: 99%